Folclore, mitologias e lendas: narrativas culturais para promoção de destinos turísticos? - Marshall, Tuanni Novaes (Universidade Federal de São Carlos, 2021)
The present project deals with ancient urban legends passed from generation to generation in important tourist destinations in different countries. Cultural stories are important decision makers in choosing travel destinations and are important for the tourism marketing and cultural heritage of each destination. For the accomplishment of this work, bibliographical research of authors in the anthropological branch and study on the planning of tourism marketing were used. The idea of the project is to give voice to storytellers and understand what is the relevance for the tourist segment.
Folklore, mythologies and legends: cultural narratives to promote tourist destinations?
Folclore, mitologías y leyendas: ¿narrativas culturales para promover destinos turísticos?
Keywords: Narrativas Culturais; patrimônio cultural; marketing turístico; destinos turísticos; imagem de destinos; Urban legends; cultural heritage; tourist destinations; marketing; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::MERCADOLOGIA; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA URBANA; CIENCIAS SOCIAIS APLICADAS::TURISMO; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA URBANA; OUTROS::CIENCIAS SOCIAIS; OUTROS::ESTUDOS SOCIAIS